Internal Mobility in New Zealand - Suzi Kerr; Dave Maré; William Power; Jason Timmins (New Zealand Government, The Treasury, 2001)
What characteristics push people to move and what pulls them to a new location? Evidence from the US has suggested that people are pulled to cities with a high population density and with large concentrations of skilled people. But how does this apply to New Zealand? Where are people moving to and from and what are the characteristics associated with the migrants' origins and destinations? This paper investigates the effect that the characteristics of a community have on the likelihood of people leaving and/or travelling to the community. The movement of people is obtained from a mobility table produced from census data by Statistics New Zealand. We use geographical information system (GIS) tools to define variables based on aggregations of meshblocks around the area units of interest. How does migration vary geographically across New Zealand? We model migration decisions and investigate their causes. Who moves and where do they go? We investigate the broad characteristics of areas that exhibit high losses and/or gains in population through migration. We investigate the relationship between the level of turnover or 'churning' of people with the characteristics of the population in that area.
Keywords: 330